Prospective follow up of children with anorectal malformation: our center experience until 10 years of age. - Leili Mohajerzadeh; Mohsen Rouzrokh; Ahmad Khaleghnejad Tabari; Alireza Mirshemirani; Naser Sadeghian; Javad Ghoroubi; Fatollah Roshanzamir; Alireza Mahdavi; Maryam Kazemi; Sayeh Hatefi; Arameh Abbasian (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2017)
Introduction: the aim of our study was to perform a longitudinal follow-up in patients with anorectal malformations(ARMs) in order to determine the anorectal function problems and help to solve them. Material and Methods: This study included 262 patients with ARM who were operated between 2006 until 2013.Children whose definitive reconstruction was performed at another hospital and underwent reoperation in our center were excluded. Patients who expired or did not come for follow-up were not included in the study either. Bowel function was prospectively assessed by using a questionnaire answered by the children's parents. supplementary bowel management with enemas, laxatives and the use of diapers were documented as well. Results: Interviews were completed in 242 children, ages ranging from 3 to 10 years. More than thirty seven (37.7%) patients had constipation.32.5% Grade 1 (controllable by altering in diet), 54.3% Grade 2 (requiring laxatives) and 13.2% Grade 3(opposed to stool softeners and diet). 18.6% of patients had fecal soiling, 31.5% Grade 1: infrequently (once or twice for every week), 24% Grade 2: daily (no community difficulty) and 44.5% Grade 3: Constant (social problem). Conclusion: In the present study several bowel function problemswere found in ARM children. physicians who perform the definitive operation on anorectal malformations should  notloose follow up of patients as they grow upbecause they may present with  great troubles during their adolescence.